Lower values of handgrip strength and adductor pollicis muscle thickness are associated with hepatic encephalopathy manifestations in cirrhotic patients - Augusti, L. [UNESP]; Franzoni, L. C. [UNESP]; Santos, L. A.A. [UNESP]; Lima, T. B. [UNESP]; Ietsugu, M. V. [UNESP]; Koga, K. H. [UNESP]; Moriguchi, S. M. [UNESP]; Betting, L. E. [UNESP]; Caramori, C. A. [UNESP]; Silva, G. F. [UNESP]; Romeiro, F. G. [UNESP] (Springer Nature, 2016)
Hepatic encephalopathy (HE) is a late complication of liver cirrhosis and is clearly associated with poor outcomes. Chronic liver insufficiency leads to progressive muscle wasting, impairing ammonia metabolism and thus increasing the risk for HE. Given the association between lean mass and adductor pollicis muscle thickness (APMT), it has been used to predict outcome and complications in many conditions, but not yet in cirrhotic patients. Therefore, this article aimed to study the association between HE manifestations and measures related to muscle mass and strength. This cross-sectional study included 54 cirrhotic outpatients with HE varying from subclinical to grade II according to the West-Haven criteria, who were submitted to neuropsychometric tests, electroencephalogram, brain Single Photon Emission Computed Tomography (SPECT), anthropometric measurements, handgrip strength (HGS) and dual energy X-ray absorptiometry exam (DXA). Multiple logistic regression analysis was performed to investigate the association between body composition measures and HE grade. Analysis of the area under the receiver operator characteristic (AUROC) curve revealed the values related to neurological manifestations (HE grades I and II). Reductions in APMT and HGS were associated with higher HE grades, suggesting a big impact caused by the loss of muscle mass and function on HE severity. The link between HE manifestations and anthropometric measures, namely APMT and HGS, point to a significant relation concerning skeletal muscles and the neurological impairment in this population.
Keywords: Anthropometry; Hepatic encephalopathy; Liver cirrhosis; Muscle strength